CHARACTERISTICS AND STANDARDS OF SOFTWARE QUALITY (INTERNATIONAL SCIENCE REVIEWS. NATURAL SCIENCES AND TECHNOLOGIES SERIES, 2025)
To attain the envisioned level of software quality, it becomes imperative to possess information concerning the prevailing standards within this domain and adhere to them across all stages of the software life cycle. This research underscores the significance of implementing standards in the realm of software quality. Over the past two decades, the InternationalOrganization for Standards has played a pivotal role in shaping quality standards for numerous software products. The commencement of this study involves a succinct overview of the evolution of standards in software quality, followed by an exhaustive examination of the present ISO/IEC standard series known as SQuaRE. This domain holds substantial importance as familiarity with software quality standards and their practical application contributes to the creation of resilient and widely adopted high-quality software. The utilization of the outlined standards and the methodologies for assessing software quality hinge on the available resources for executing the method. These resources encompass factors such as time, financial means, the quantity of evaluators and their proficiency, the volume of users for testing, as well as the accessibility of facilities and testing equipment. Additionally, the chosen level of objectivity and its applicability across diverse stages of application development play a crucial role in determining how these standards and evaluation approaches are implemented.